INTERNAL TERMS OF TRADE FOR CITRUS PRODUCTION IN TURKEY (Third Sector Social Economic Review, 2018)
The agriculturesector is considered not only as a sectorthatmeets the nutritionalneeds of the rapidlyincreasing urban population but also as an importantresourcethatwillprovidefinancing for economicdevelopment. The direction of intersectoralresource transfer is importantin terms of keeping the sectorsunderinflationarypressure. Balanceddevelopment in the economy is possiblewith the input and outputrelations of the sectors, i.e. sectoraldistributionrelations. The internalterms of tradeareone of the indicatorsusedtodetermine the direction of resource transfer betweensectors. Theinternalterms of tradeare of greatimportance in terms of showingthe changes in the economicwelfare of the agriculturalsector. For thisreason, it is veryimportantthat the agriculturalpoliciesaremadebytakingintoconsiderationthe internalterms of trade. Inthisstudy, it wasaimedtodetermine the change in the internalterms of trade of citrusproductsduring the period of 2003-2017. The internalterms of trade for citrusproductswerecalculatedaccordingto the in-countryproducerpriceindex and the farmers' priceindex in the context of net changerates. As of the researchperiod, the internalterms of tradehavefollowed a course in favor of agriculture, but there has been a decrease in the terms of domestictrade for citrus. When the internalterms of tradeareexaminedaccordingto the pricesreceivedbyfarmers’ index for the agriculturalsector, it can be saidthat the citrusfarmer is moreaffectedby the changes in prices. During the periodunderreview, the rate of citrusproducersaffectedby the increase in inflationwasincreased and therewas a significantdecrease in realpurchasingpower.Support for citrusproductsshould be increased.Fertilizer, dieseloil and certifiedseedlingssupport is veryimportant for the citrusproducers not tofallunder the pricepressure and to be affectedless.
Keywords: Prices received by farmers; Internal Terms of Trade; Citrus